Ethnopedagogy-Based English for Tourism Teaching Techniques - Abdul Baqi, Fuad; Rohmiyati, Yuli (Center of Language and Cultural Studies, 2023)
Ethnopedagogy is a learning trend that integrates learning and local wisdom, including in teaching English. This study aims at analysing the Ethnopedagogy- Based Teaching Technique for the subject of English for Tourism in the English Education Study Program, Faculty of Teacher Training and Education, University of Banten Jaya. Data were obtained through observation and interviews with 2 lecturers who teach English for Tourism. From the results of observations and interviews obtained 7 techniques in teaching, namely (1) Picture Describing, (2) Brainstorming, (3) Interview, (4) Role-Play, (5) Storytelling, (6) Find the Difference, and (7) Reporting. In the Implementation, the lecturers always connect with local wisdom in Banten area.